Pharmaceutical Study on Jwarankusa Rasa (International Journal of Ayurveda and Pharma Research, 2022)
Rasayogas in Ayurveda have a wide range of therapeutic utility since they are fast acting even in smaller doses. Acharya Charaka mentioned, Jwara is the foremost of all diseases, so it need a special attention. There are various herbal and herbomineral preparation mentioned for Jwara chikitsa mentioned in Brihat trayees, Laghu trayees. Wide variety of Rasa yogas were mentioned in classics for Jwara and Jwarankusa rasa is one among them. Herbomineral preparations mentioned for Jwara have specific mode of action including Ama pachana, Agni vardana, Sroto sodhana and Jwara hara properties. Jwarankusa rasa is a well known herbo mineral formulation specially indicated for Vishama jwara and it is mentioned on Bhaishajya Ratnavali Jwara chikitsa. There are various references available for Jwarankusa rasa with various ingredients and different method of preparation such as Rasendra sara sangraha, Rasa Prakasha sudharakara, Sharangadhara Samhita, Vrinda nigantu ratnakara, Rasa chandamsu. In certain references Jwarankusa rasa consists of only non-herbal ingredients and in other references we can find it as herbomineral combination. Majority of the Yogas contains ingredients such as Parada, Gandhaka, Tankana, Haritala, Manasila among the non-herbal ingredients and Vatsanabha, Sunti, Danti beeja, Dattura beeja among the herbal ingredients. It is mainly indicated in diseases such as Jwara, Jwaratisara, Vishama jwara, Vishoochika. Rasa dravyas are Rasayana yogavahi and possess Amadosha nirharana property. Preparation and observations during preparation of Jwarankusa rasa mentioned in Bhaishajya Ratnavali Jwara chikitsa is emphasized in this humble work.